Pengaruh Zat Pengatur Tumbuh dan Pupuk Kandang Sapi Terhadap Pertumbuhan dan Produksi Tanaman Kacang Hijau (Vigna radiata L.) - Laia, Repu; Zulfida, Ida; Linda Br Jabat, Yelfi Yana (JURNAL AGROPLASMA, 2024)
This study aimed to enhance mung bean productivity through the combination of organic fertilizer (cow manure) and plant growth regulators (ZPT). Using a Randomized Complete Block Design (RCBD), this study tested the effects of different doses of cow manure and ZPT on the growth and yield of Vima 5 mung bean variety. The results showed that cow manure had a more significant positive effect than PGRs in increasing pod weight per plant. Although visual observations indicated increased growth, there were no statistically significant differences between treatments. This study concludes that the use of cow manure can be a good alternative to improve mung bean productivity, but further research is needed to optimize the combination of cow manure and ZPT doses. Keywords: mung bean, ZPT, cow manure